CERKL regulates autophagy via the NAD-dependent deacetylase SIRT1. Issue 3 (4th March 2019) - Hu, Xuebin; Lu, Zhaojing; Yu, Shanshan; Reilly, James; Liu, Fei; Jia, Danna; Qin, Yayun; Han, Shanshan; Liu, Xiliang; Qu, Zhen; Lv, Yuexia; Li, Jingzhen; et al.
ABSTRACT: Macroautophagy/autophagy is an important intracellular mechanism for the maintenance of cellular homeostasis. Here we show that the CERKL (ceramide kinase like) gene, a retinal degeneration (RD) pathogenic gene, plays a critical role in regulating autophagy by stabilizing SIRT1. In vitro and in vivo, suppressing CERKL results in impaired autophagy. SIRT1 is one of the main regulators of acetylation/deacetylation in autophagy. In CERKL-depleted retinas and cells, SIRT1 is downregulated. ATG5 and ATG7, 2 essential components of autophagy, show a higher degree of acetylation in CERKL-depleted cells. Overexpression of SIRT1 rescues autophagy in CERKL-depleted cells, whereas CERKL loses its function of regulating autophagy in SIRT1-depleted cells, and overexpression of CERKL upregulates SIRT1. Finally, we show that CERKL directly interacts with SIRT1, and may regulate its phosphorylation at Ser27 to stabilize SIRT1. These results show that CERKL is an important regulator of autophagy and it plays this role by stabilizing the deacetylase SIRT1.